2019
DOI: 10.1177/1748048519883520
|View full text |Cite
|
Sign up to set email alerts
|

Refugee debate and networked framing in the hybrid media environment

Abstract: In this article, we analyse how the debate on the ‘refugee crisis’ has been constructed in Finnish news media and social media by using big data analytics. The study applies big data with the aim of exploring the dynamics between the mainstream news media and social media and the ways in which these dynamics shape and strategically amplify different understandings of the refugee crisis. The research highlights over-emphasis of crime and threat-oriented themes on refugee issues in social media, as well as illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Moreover, while I was not able to identify any prevailing emotional component in the media frames, such as fear or trust, the results of the study do suggest that the majority of the migration frames in social media were more likely to trigger negative emotions, in contrast to the official newspapers where positively loaded frames were more common. The results of the study provide some implicit evidence that these frames could serve to articulate hostile and ethnically prejudiced narratives about migrants and refugees, which supports earlier evidence (Ladner et al, 2019; Pöyhtäri et al, 2019; Siapera et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, while I was not able to identify any prevailing emotional component in the media frames, such as fear or trust, the results of the study do suggest that the majority of the migration frames in social media were more likely to trigger negative emotions, in contrast to the official newspapers where positively loaded frames were more common. The results of the study provide some implicit evidence that these frames could serve to articulate hostile and ethnically prejudiced narratives about migrants and refugees, which supports earlier evidence (Ladner et al, 2019; Pöyhtäri et al, 2019; Siapera et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, another study of sentiments expressed in tweets has revealed a prevalence of negative sentiments in the messages related to the crisis (Ladner et al, 2019). Social media framing of the topic has been found to be dominated by crime and threat narratives (Pöyhtäri et al, 2019), while migrants and refugees have often been perceived as a security threat (Siapera et al, 2018) or as “illegals” and “terrorists” (Gualda & Rebollo, 2016). In Sweden and elsewhere, it has been reported that social media was providing platforms for the articulation of racist and right-wing discourses (Ekman, 2014; Merrill & Åkerlund, 2018; Topinka, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Islamophobic and xenophobic sentiments and related hate speech have become prominent in public debates, especially after ISISbacked terroristic attacks in several European cities in 2015-2017 as well as during and after the European "refugee crisis" in 2015 (e.g., Berry et al, 2015;Baider et al, 2017). Hate speech targeting various ethnic, migrant, and religious minorities flourishes especially in general social media discussions (for the Finnish context, see Pöyhtäri et al, 2019), but it has also long taken the forms of organized propaganda, hate groups, and hate sites (Roversi, 2008;Daniels, 2009;Citron, 2014;Anat and Matamoros-Fernandez, 2016;Brown, 2018;Farkas and Neumayer, 2018).…”
Section: Definitions and Research On Hate Speechmentioning
confidence: 99%
“…While the debate on how social media affects news dissemination is still ongoing, one dynamic that has relevance for our study is that social media has been found to polarize those news that do end up in public debate. For example, a recent study in Finland found that social media over-emphasized news articles with crime and threat-oriented themes on refugee issues, while positive articles about refugees where under-emphasized [47].…”
Section: Prior Work On the Role Of Public Debate In The Mediamentioning
confidence: 99%